2021
DOI: 10.1101/2021.09.17.460763
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MinION nanopore sequencing provides similar methylation estimates to Sanger bisulfite sequencing in the TRPA1 promoter region

Abstract: Bisulfite sequencing has long been considered the gold standard for measurement of DNA methylation at single CpG resolution. In the meantime, several new approaches have been developed, which are regarded as less error-prone. Since these errors were shown to be sequence-specific, we aimed to verify the methylation data of a particular region of the TRPA1 promoter obtained from our previous studies. For this purpose, we compared methylation rates obtained via direct bisulfite sequencing and nanopore sequencing.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Sanger sequencing has some upsides, such as still being the gold standard of comparison as well as the effective investigation of specific genetic loci. Concerning the method’ s accuracy for measuring single promoter regions, our research group showed that Sanger sequencing achieves comparable results compared with (ONT-S) when analyzing promoter methylation [55].…”
Section: Discussionmentioning
confidence: 99%
“…Sanger sequencing has some upsides, such as still being the gold standard of comparison as well as the effective investigation of specific genetic loci. Concerning the method’ s accuracy for measuring single promoter regions, our research group showed that Sanger sequencing achieves comparable results compared with (ONT-S) when analyzing promoter methylation [55].…”
Section: Discussionmentioning
confidence: 99%